226 Geospatial analysis of cattle maternal behavior during fenceline weaning as influenced by dam age and maternal behavior at calving. (7th December 2018) - Rutherford, W; Parish, J; Smith, T; Vann, R; Strickland, B
Abstract: The study objective was to assess the effect of maternal behavior at calving on dam behavior during fence-line weaning. Crossbred cattle (n = 37) were fitted with global positioning system (GPS) collars on the day of weaning their calves and placed in a 10.1-ha pasture adjacent to their calves and separated by a common fence. Dam position was recorded at 5-minute intervals for 14 d. Dam distance from the fence was analyzed using SAS PROC MIXED. Mean distance from the fence was greater ( P < 0.01) each day for first-calf heifers (n = 19) than for multiparous cows (n = 18). Both maternal aggression score during calf handling within 24 h of calving (MA : 1 = flight response to 5 = fight response) and mothering aptitude score immediately following calf processing at calving (MOM : 1 = calf abandonment, 2 = cow retreats quickly with calf, 3 = cow flees chasing calf, 4 = cow walks away with calf, 5 = cow stays in immediate area with calf) affected mean daily distance to the fence ( P < 0.01). Dams assigned a MA of 2 maintained a greater mean daily distance from the fence than contemporaries ( P < 0.01). Daily distance from the fence was greatest ( P < 0.01) for calves born to dams with a MOM of 2 or 5 ( P < 0.01). Dams with a MOM of 3 kept closest to the fence ( P < 0.01). As day post-weaning increased, mean distance from the fence increased for both heifers and cows linearly ( P < 0.01). Differences between LSMEANS of dam distance to the fence by day became less ( P < 0.01) after day 5. This suggests the duration for fence-line weaning should exceed 5 d, and relationships between maternal behavior at calving and weaning may exist.